Back Cover: Plasma Process. Polym. 4∕2014. Issue 4 (April 2014) - España‐Sánchez, Beatriz L.; Ávila‐Orta, Carlos A.; Padilla‐Vaca, Felipe; Neira‐Velázquez, María G.; González‐Morones, Pablo; Rodríguez‐González, José A.; Hernández‐Hernández, Ernesto; Rangel‐Serrano, Ángeles; Barriga‐C., Enrique Díaz; Yate, Luis; Ziolo, Ronald F.
<x xml:space="preserve">Abstract</x> Back Cover: Argon plasma treatment of poly(propylene)/silver and poly(propylene)/copper nanocomposites increases the exposure of surface nanoparticles. Plasma treatment removes the polymer from the nanoparticle surface, exposing the metallic nanoparticles, modifying the surface properties and increasing the antimicrobial properties of nanocomposites against pathogenic bacteria, an important issue in health care applications. Further details can be found in the article by Carlos Alberto Ávila Orta et. al. on page 353. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>